Obesity and the Risk of Cryptogenic Ischemic Stroke in Young Adults - Jaakonmäki Nina; Zedde Marialuisa; Sarkanen Tomi; Martinez-Majander Nicolas; Tuohinen Suvi; Sinisalo Juha; Ryödi Essi; Autere Jaana; Hedman Marja; Junttola Ulla; Huhtakangas Jaana K; Grimaldi Teresa; et al. (Elsevier, 2022)
Objectives
We examined the association between obesity and early-onset cryptogenic ischemic stroke (CIS) and whether fat distribution or sex altered this association.
Materials and Methods
This prospective, multi-center, case-control study included 345 patients, aged 18-49 years, with first-ever, acute CIS. The control group included 345 age- and sex-matched stroke-free individuals. We measured height, weight, waist circumference, and hip circumference. Obesity metrics analyzed included body mass index (BMI), waist-to-hip ratio (WHR), waist-to-stature ratio (WSR), and a body shape index (ABSI). Models were adjusted for age, level of education, vascular risk factors, and migraine with aura.
Results
After adjusting for demographics, vascular risk factors, and migraine with aura, the highest tertile of WHR was associated with CIS (OR for highest versus lowest WHR tertile 2.81, 95%CI 1.43-5.51; P=0.003). In sex-specific analyses, WHR tertiles were not associated with CIS. However, using WHO WHR cutoff values (>0.85 for women, >0.90 for men), abdominally obese women were at increased risk of CIS (OR 2.09, 95%CI 1.02-4.27; P=0.045). After adjusting for confounders, WC, BMI, WSR, or ABSI were not associated with CIS.
Conclusions
Abdominal obesity measured with WHR was an independent risk factor for CIS in young adults after rigorous adjustment for concomitant risk factors.